The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/ol0171564
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phosphate Chemosensor Utilizing Anion-Induced Fluorescence Change

Abstract: [structure: see text] The neutral receptor N,N'-bis[3,5-di[(1-pyrenylmethyl)carbamoyl]benzyl] pyridine-2,6-dicarbamide (2) provides a pseudo-tetrahedron cleft and multiple hydrogen bondings to form a 1:1 complex with phosphate ion in a highly selective manner, by comparison with other anions (F(-), Cl(-), Br(-), SCN(-), AcO(-), NO(3)(-), ClO(4)(-), and HSO(4)(-)). The binding strength can be inferred from the emission intensity ratio of the pyrene monomer (lambda(max) 377 nm) to the excimer (lambda(max) 477 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…[23] The anion that was bound to with the amino group of 2·Cu I should reduce its participation in PET quenching of the naphthalene, and thus enhance the fluorescence emission. Moreover, no excimer emission was observed owing to the insertion of anions that caused the two naphthalenes to move away from each other.…”
Section: Full Papermentioning
confidence: 99%
“…[23] The anion that was bound to with the amino group of 2·Cu I should reduce its participation in PET quenching of the naphthalene, and thus enhance the fluorescence emission. Moreover, no excimer emission was observed owing to the insertion of anions that caused the two naphthalenes to move away from each other.…”
Section: Full Papermentioning
confidence: 99%
“…Its function is based on the fact that in one of the sensor states, when with bound or unbound target molecules, the two fluorophore molecules are close to each other but distant enough to form an excimer upon excitation, while in the other state they move apart and excimers are not observed. This was the idea of Yang et al in the construction of sensors for cations (Yang, Lin et al, 2001;Liao, Chen et al, 2002) when constructing a sensor for anions. Furthermore, since pyrene is a fluorophore that can easily form excimers, it has been used for the construction of sensors for DNA detection, as described by Mahara et al (Mahara, Iwase et al, 2002) as it needs the formation of pyreneconjugated oligonucleotides where excimers can occur or in sensor for protein-protein recognition, as described by Sahoo et al (Sahoo, Narayanaswami et al, 2000) Martins et al (Martins et al, 2011 in press) showed that peptide nanostructures containing pyrene derivatives sorbed onto them can sense distinct environments, with effect on fluorescence lifetimes, even when excimer are not formed.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%
“…]DMSO), [26] and amido-pyrrole-based receptors (K H 2 PO 4 À/K OAc À = 5-30 also in [D 6 ]DMSO). [27][28][29] …”
Section: Introductionmentioning
confidence: 99%